A estação arqueológica dos Penedos Grandes, Arcos de Valdevez (Norte de Portugal) : notícia preliminar - Bettencourt, Ana; Dinis, António; Silva, Isabel Sousa e; Cruz, Carlos; Pereira, José; Martins, Josélia (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
This article draws upon the recent archaeological excavations at the site of Penedos Grandes (Arcos de Valdevez), which has previously been excavated at the beginning of the twentieth century. The site is a mountain Bronze Age settlement, which has been occupied for a short term.